Modeling the Formation of Liposomes with Vinpocetine from Soy Lecithin Phospholipids by Molecular Dynamics - Yu. A. Polkovnikova (Разработка и регистрация лекарственных средств)
Introduction. Liposomal preparations have the following advantages: they protect body cells from the toxic effects of drugs; prolong the action of the drug introduced into the body; protect medicinal substances from degradation; promote the manifestation of targeted specificity due to selective penetration from blood into tissues; change the pharmacokinetics of drugs, increasing their pharmacological effectiveness; allow you to create a water-soluble form of a number of medicinal substances, thereby increasing their bioavailability. The development of liposomal forms of vinpocetine is highly relevant. Currently, when developing the composition of liposomal forms, molecular modeling methods are widely used, which are a convenient method for predicting both the properties of the membranes themselves and aspects of the interaction of membranes with small molecules or proteins.Aim. The aim of this study is to model the process of liposome assembly from soy lecithin phospholipids in the presence of vinpocetine by the molecular dynamics method; as well as predicting the distribution of vinpocetine between the internal cavity of the liposome, the phospholipid membrane, and the dispersion medium based on the simulation results.Materials and methods. To simulate the process of liposome formation, the method of coarse-grained molecular dynamics in a Martini 2.2 force field was used using the Gromacs 2016.4 program. The assembly of the simulated system - a solution of soy lecithin phospholipids in water was performed using the Internet service Charmm-GUI-> Inputgenerator-> Martinimaker-> Randombuilder.Results and discussion. The results of molecular modeling showed that the vinpocetine molecules did not penetrate into the liposome, but were adsorbed on its surface. This is due to the low solubility of vipocetin in the hydrophobic medium of the soy lecithin liposome membrane.Conclusion. It was shown that the minimum diameter of a liposome formed from purified soy lecithin is 15.3 nm. Vinpocetine does not penetrate into liposomes from purified soy lecithin, but is adsorbed on the outer surface of their membrane. The surface excess in this case, according to the results of modeling coarse-grained molecular dynamics at a temperature of 298 K in an alcohol-water medium, is 1.2 • 10-7 mol/m2.